A study on the applicability of batik for public transportation design in Indonesia - Yukhi Mustaqim Kusuma Syabana; Gun Bae Park (National Research and Innovation Agency, 2020)
This paper attempts to grant Indonesian identity in the development and importing the public transportation equipment from overseas. We reviewed and surveyed the present state issues of Indonesian public transportation equipment design development. The study analyzed the philosophical values of batik in a modern way, the possibility of batik application for important regionalism identity, and identity in design development strategy. As a result, we gather and assess the philosophical values of Batik motifs that contain geographic origin, the essences, and characteristics to be applied as design element strategies. We found the regional identity of the historical, local wisdom essence, acculturation, various colors, and original shapes of the Batik motifs. Moreover, Indonesian fancy design is also supported by other possibilities indigenous material and technique that usually used, particularly in Indonesia. These possibilities were identically Indonesian and also applicable as the sustainable public transport equipment design identity issue solution. This effort was conducted as the turning point to solve the issues of public transport equipment design strategies dependency. Thus, this research will be helpful for aesthetics research in the modern way of the public transportation equipment design concept.